PECULIARITIES OF ORGANIZATIONAL STRATEGY FORMATION - Togayev, Salim; Ergashev, Jasur (Educational Research in Universal Sciences, 2023)
The article presents the results of a critical analysis of methodological approaches to the formation of organizational development strategies.